التكرار في القرآن الكريم في منظور بديع الزمان سعيد النورسي - Dimyathi, Muhammad Syairozi; Elmaula, Inayah; Tabroni, Hananah Muhtar (Islamic Religious Education Departement, 2022)
Repetition in the Holy Qur’an is one of the topics that concern some orientalists, as they claim that the Holy Qur’an is a book that raises doubts that it is from God Almighty because of the many repetitions in it as if God Almighty has no other expressions to highlight His purposes and is forced to repeat some verses. According to Saeed Nursi, the research aims to reveal the rule of repetition in the Holy Qur’an because of his unique insight into the phenomenon of Qur’anic repetition. In this research, the inductive analytical method is used, where the views of Said Nursi about repetition in the Holy Qur’an and the wisdom behind it were extrapolated and analyzed through his writings in the Rasa’il al-Nur. Among the results of this research is that Saeed Nursi provided a full explanation of the ruling on repetition of the Qur’anic verses, in the luminous miraculousness in the repetitions of the Qur’an, in six main points, namely: that repetition in the Holy Qur’an is better and more eloquent and even more necessary than others; Behind this repetition are Qur’anic purposes; It is considered one of the human moral needs. It is for confirmation, determination, and endorsement; It is a repetition in different forms; It is done in various ways. Nursi also showed that repetition in the Holy Qur’an is for the sake of not being bored and bored, as it came to establish, and that it sends psychological and aesthetic pleasure in the hearts of readers and listeners. Thus, Saeed Nursi came up with something new that no other scholars had preceded in their statement of the ruling on repetition in the Holy Qur’an.